SOCIO-PHILOSOPHICAL ISSUES IN THE DEVELOPMENT OF CIVIL SOCIETY IN THE NEW UZBEKISTAN (American Journal of Research in Humanities and Social Sciences, 2024)
Large-scale reforms are being implemented in the new Uzbekistan in order to create a free civil society and build a humane democratic rule of law state. The main purpose of these reforms is to glorify human dignity, ensure its rights and interests, and their social protection. A striking example of this is that the glorification of a person, the expression of his rights and legitimate interests, and comprehensive development are accepted as the main factor in all reforms implemented in our country. Modern conditions created for people, buildings, squares, avenues and streets in the form of national design attract everyone's attention. Increasing the responsibility of every citizen of society in the implementation of these processes, building a civil society in accordance with national values and traditions has become a requirement of the time. Confidence in the future of the country in the psyche of the people is increasing every day, the philosophical way of thinking of people is changing. The moral environment based on social protection has stabilized, and consistent work has begun to strengthen the role of non-governmental organizations. A scientific and practical approach has been formed to the role of civil society institutions in educating the young generation of the new Uzbekistan with perfect people in all aspects, as well as the organization of clusters such as production, industry, agriculture, agriculture, animal husbandry, aimed at realizing the aspirations of people in the regions, has begun to bring its positive effect. This has opened up wide opportunities for people to take a step towards civil society.